ChemInform Abstract: Exceptional Activity of Gallium(III) Chloride and Chlorogallate(III) Ionic Liquids for Baeyer—Villiger Oxidation. Issue 31 (14th July 2016) - Markiton, Magdalena; Chrobok, Anna; Matuszek, Karolina; Seddon, Kenneth R.; Swadzba‐Kwasny, Malgorzata
Abstract: The Baeyer—Villinger oxidation of cyclic ketones with H2 O2 as oxidizing agent using a range of metal chlorides in different solvents or neat chlorogallate(III) ionic liquids is investigated.